Kritische Diskussion zur bisherigen Qualitätsdebatte in der Langzeitpflege: ein Plädoyer für eine systemische und auf empirischen Erkenntnissen beruhende Betrachtung der Entwicklung und Messung von Qualität in der Langzeitpflege - Hasseler, Martina (Zeitschrift für Gerontologie und Geriatrie, 2019)
Against the background of the quality debates on long-term care and recurrent reform measures in politics on this topic, a critical discussion on the current state of quality development, testing and reporting in Germany is presented. In Germany, the linear model of Donabedian’s structural, process and outcome quality is still used as a basis for quality issues in nursing care; however, international research suggests that multiple and mutually interacting factors influence nursing quality and that a more systematic and systemic perspective for the further development of nursing quality (especially of features, criteria and indicators of nursing quality) appears more appropriate. This article intends to open the perspective of the development, measurement and reporting of quality in nursing and to make a critical contribution for a systemic theory development as a relevant basis for future developments of quality evaluation programs and quality reporting systems in long-term care.